Bilinearity, rules, and prefrontal cortex - Peter Dayan (Frontiers in Computational Neuroscience, 2007)
Humans can be instructed verbally to perform computationally complex cognitive tasks; their performance then improves relatively slowly over the course of practice. Many skills underlie these abilities; in this paper, we focus on the particular question of a uniform architecture for the instantiation of habitual performance and the storage, recall, and execution of simple rules. Our account builds on models of gated working memory, and involves a bilinear architecture for representing conditional input-output maps and for matching rules to the state of the input and working memory. We demonstrate the performance of our model on two paradigmatic tasks used to investigate prefrontal and basal ganglia function.